2016
DOI: 10.48550/arxiv.1612.07479
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of $P_c^+(4380)$ and $P_c^+(4450)$ as pentaquark states in the molecular picture with QCD sum rules

K. Azizi,
Y. Sarac,
H. Sundu

Abstract: To better understand the nature and internal structure of the exotic states discovered by many collaborations, more information on their electromagnetic properties and their strong and weak interactions with other hadrons is needed. The residue or current coupling constant of these states together with their mass are the main inputs in determinations of such properties. We perform QCD sum rules analyses on the hidden-charm pentaquark states with spin-parities J P = 3 2 ± and J P = 5 2 ± to calculate their resi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 49 publications
(63 reference statements)
1
13
0
1
Order By: Relevance
“…It has been suggested that their decay patterns could be used to distinguish among various hadronic molecular options (Lin et al, 2017;Shen et al, 2016;Wang et al, 2016a). There are also other dynamical studies with different channel bases (Azizi et al, 2016;Geng et al, 2017;Xiao, 2017;Yamaguchi and Santopinto, 2017).…”
Section: Pentaquark-like Structures With Hidden-charmmentioning
confidence: 99%
“…It has been suggested that their decay patterns could be used to distinguish among various hadronic molecular options (Lin et al, 2017;Shen et al, 2016;Wang et al, 2016a). There are also other dynamical studies with different channel bases (Azizi et al, 2016;Geng et al, 2017;Xiao, 2017;Yamaguchi and Santopinto, 2017).…”
Section: Pentaquark-like Structures With Hidden-charmmentioning
confidence: 99%
“…In particular, the composite structure of the new exotic states has been studied using coupled-channel dynamics [6,7]. An application of QCD sum rules to hidden charm pentaquark states has been done in [8] using diquark-diquark-antiquark type interpolating currents, in [9][10][11] with meson-baryon molecular type currents, and the currents in form of product of two color-octet clusters of three light quarks and charm-anticharm pair [12]. Double polarization observables in pentaquark photoproduction have been studied by JPAC Collaboration using reaction model in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The masses of these states were very close to D * Σ * c threshold. This makes comfortable to assume that those two pentaquarks as baryon-meson molecule [9][10][11][12][13][14][15][16][17][18][19]. The other possibilities are compact pentaquark [20][21][22][23], quark model [24][25][26], chiral quark model [27], quark-cluster model [28] and baryocharmonium model [29].…”
Section: Introductionmentioning
confidence: 99%